Priority based tag authentication and routing algorithm for intermodal containers RFID sensor network - Andziulis, Arūnas; Plėštys, Rimantas; Jakovlev, Sergej; Adomaitis, Danielius; Gerasimov, Konstantin; Kurmis, Mindaugas; Pareigis, Valdemaras (Transport, 2012)
Intermodal containers transportation management has always been a serious issue among logistics worldwide companies where the application of secure mobile information technologies (e.g. radio frequency identification systems (RFID) and sensor networks) could significantly improve the current situation by sending managers all the needed transportation conditions information. In this paper, we have focused on improving managerial decision making method by introducing the expert system evaluation functionality in a common software solution CTRMS for additional ICT risks evaluation. The basic risks involved in transportation and the appropriate measures are introduced as well. The pre-defined RFID sensor network was used to develop an optimal tag authentication and routing algorithm where tags and reader authentication protocols were defined and based upon the highest security assurance and the reader to tag response time criterias. A Nearest Neighbor (NN) heuristic approach and a Priority setting method were used to address the problem of routing within the RFID sensor network between tags with the objective function of minimizing the data transfer time between tags with the highest priority values. Computational results also indicate that when the tags have the same level of confidence in the system, they can exchange information without any additional verification, so making the authentication protocol less time consuming and therefore more effective against other proposed protocols. First Published Online: 21 Dec 2012